2021
DOI: 10.1186/s12889-020-10138-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health status in relation to aircraft noise exposure, noise annoyance or noise sensitivity: the results of a cross-sectional study in France

Abstract: Background Noise is a major public health issue because of its negative impacts on health, including annoyance, sleep disturbance, cardiovascular diseases and altered cognitive performance among children. Self-rated health status (SRHS) can be considered as a reliable indicator of quality of life, morbidity and mortality but few studies have considered SRHS in relation to aircraft noise exposure. The present study aims to investigate the association between this exposure and SRHS of people livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
(70 reference statements)
0
18
0
1
Order By: Relevance
“…Earlier research established a link between socio-demographic status and perceived noise exposure [ 11 , 12 , 25 , 26 ]. Additionally, several studies assessed self-reported noise-related health status using socio-demographic data [ 1 , 13 , 21 ]. Our findings revealed that younger individuals reported more noise-related health problems, similarly as in another study that found that younger persons may be more likely to be impacted by noise [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier research established a link between socio-demographic status and perceived noise exposure [ 11 , 12 , 25 , 26 ]. Additionally, several studies assessed self-reported noise-related health status using socio-demographic data [ 1 , 13 , 21 ]. Our findings revealed that younger individuals reported more noise-related health problems, similarly as in another study that found that younger persons may be more likely to be impacted by noise [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The draft questionnaire was developed using previous research and discussion with experts [ 1 , 3 , 4 , 5 , 6 , 18 , 19 , 20 , 21 ]. Additionally, a pilot survey was conducted among a sample of university students to validate the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…), were based on flight information and supported by measurements taken at several monitoring stations around the airport. The INM software used to model noise has been accredited for use in national aircraft noise monitoring and used repeatedly in health impact assessments of exposed population [ 29 ] including in the landmark HYENA study [ 7 ]. The model validity was therefore considered strong enough to use its outputs in this epidemiological study.…”
Section: Study Methodsmentioning
confidence: 99%